2023
DOI: 10.3389/fpls.2023.1194119
|View full text |Cite
|
Sign up to set email alerts
|

Validation of genes affecting rice mesocotyl length through candidate association analysis and identification of the superior haplotypes

Abstract: Mesocotyl is an essential organ of rice for pushing buds out of soil and plays a crucial role in seeding emergence and development in direct-seeding. Thus, identify the loci associated with mesocotyl length (ML) could accelerate breeding progresses for direct-seeding cultivation. Mesocotyl elongation was mainly regulated by plant hormones. Although several regions and candidate genes governing ML have been reported, the effects of them in diverse breeding populations were still indistinct. In this study, 281 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…It is widely acknowledged that mesocotyl elongation is essential for seedling emergence in rice ( Lee et al, 2017 ). A study conducted by Wang et al (2023) found that phytohormones (SLs, CKs, ABA, BRs, IAA, and JA) have a direct influence on mesocotyl elongation by affecting cell division or elongation. Likewise, Liang et al (2016) supported that an increase in endogenous gibberellin content, which in turn caused changes in cortical microtubule organization, promoted rice mesocotyl elongation.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that mesocotyl elongation is essential for seedling emergence in rice ( Lee et al, 2017 ). A study conducted by Wang et al (2023) found that phytohormones (SLs, CKs, ABA, BRs, IAA, and JA) have a direct influence on mesocotyl elongation by affecting cell division or elongation. Likewise, Liang et al (2016) supported that an increase in endogenous gibberellin content, which in turn caused changes in cortical microtubule organization, promoted rice mesocotyl elongation.…”
Section: Discussionmentioning
confidence: 99%